Developing a COVID-19-focused mHealth system in a low-resource setting during the COVID-19 pandemic: challenges and opportunities - Stenhouse, Rosie; Gebbie Beshir, Wassie; Girma, Demessie; Fida, Gosaye; Calia, Clara; Guto, Godana; Wolters, Maria Klara (Frontiers in Digital Health, 2025)
IntroductionApproximately three-quarters of Ethiopia's population lives in rural areas, and access to healthcare is difficult with poor transport infrastructure and long travel times. Telemedicine has the potential to support healthcare access and minimise COVID-19 transmission through a reduced need to travel.ObjectivesThis Brief Research Report describes the analysis of qualitative data relating to the development of a mobile health (mHealth) system during the COVID-19 pandemic to support COVID-19 symptom management in the community in Oromia, Ethiopia.MethodsData were collected from (1) meeting notes and WhatsApp group discussions, (2) a focus group with medical staff, and (3) an interview with a senior hospital leader. A framework method was used for the analysis.ResultsThree themes were identified: (1) patient–physician relationship, (2) new ways of using everyday technology, and (3) infrastructure and digital access.DiscussionWe discuss the challenges of developing an mHealth system during a pandemic alongside infrastructural challenges and the preparedness of medical staff and communities for the use of mHealth.ConclusionsThere is a need for investment in information technology infrastructure and in access to digital networks, alongside a need to improve the digital and health literacy of populations for the successful implementation of a patient-facing mHealth system. Thus, whilst the policy aspirations are admirable, the potential for technological innovation is great, and the clinicians can see the benefit of using technologies to provide care to those who cannot reach clinics, there is a gap between what is possible given the current reality of infrastructure and patient preparedness and the requirements for a successful telemedicine intervention.